Influences of Branding on Consumer Purchase Decision Making Process: An Empirical Research in Chinese Real Estate Agency Industry - Ou, Jia-Lin (2020)
Branding in marketing is a very important component. Generally, branding activities aim to stimulate potential customers to consume. Moreover, there are many literatures focus on products branding to consumers, but they ignore the importance of service branding. Products can be packaged by sellers in a beautiful box, but services could not do this like products. Because of this intangible nature of services, services branding to consumers are different from products branding. Therefore, investigation of service branding in consumers is very important. Moreover, many previous studies only focus on the results of services branding to consumers, but they ignore the consumer purchase decision making process is also important. A very relevant investigation about service branding and consumer buying decision making process has provided a service brand verdict model which has provided many important brand dimensions. Therefore, this study will base on two dimensions (brand evidences and brand hearsay) to connect with consumer buying decision making process to investigate the research question of this study. Moreover, with the development of Chinese real estate agency industry, branding becomes an important part of marketing in this industry. However, because of immature nature of this industry in China, there are limit studies to investigate in real estate agency branding and consumers purchase decision making process. Therefore, this study aims to contribute in this area. The findings of this study have many differences with the dimensions of SBV model. For example, the location and number of branches are different from the SBV model. Furthermore, hyposensitive population is a special finding in this investigation.